The growth and production responses Three Varieties of purple Sweet Potato (Ipomea batatas L.) on Giving Multiple Doses Bokashi - weldi ginting; jonatan ginting; nini rahmawati (Jurnal Agroekoteknologi, 2017)
The experiment was conducted in Desa Pasar Kawat District of Beringin Kabupaten DeliSerdang on Juny to November 2015, using a factorial randomized block design with two factors, the first factor is varieties (Antin 1, Antin 2,             Antin 3) and the second factor is doses Bokashi (0, 5, 10, 15 ton/ha).Data were analized with Analysis of Variance and continued with Duncan’s Multiple Range Test (DMRT). Observed were increase height of plant, weight tuber per plot and index of yield.The results showed that application of varieties increased weight tuber per plot, index of yield.Doses Bokashi increasing the height of plant,weight tuber per plot.Interaction of varieties and giving multiple doses bokashi source were significantly effect to average weight tuber.